Innovations and technologies for athletes` training in Elite Sport Centers - Position detection in game sports - Lames, M. (7. Forum on Elite Sport- INSEP, Paris, France, 28.August.-1. September 2011, 2011)
Position detection: 10-20 companies worldwide offer position detection in sport, widespread service in professional game sports, especially football (soccer) Germany: Association of professional football clubs provides clubs with statistics on actions and positions (and sells these statistics to other customers) Achievements • Technological innovations have made positional data available • A wealth of information is available routinely per match Still to solve • Standards for data processing (filtering techniques) • Standards for accuracy testing • Interpretation of position and speed data • Key aspect: capability to select different situations - Running game / interrupted game - Offence / Defense - Set game / fast break / position game - Playing position